Comparison of stainless steel and nickel-titanium coil springs effects on the space closure rate (in vitro study) - Fadhil Y Jasim; Wafaa Gh Al-Shahery (University of Mosul, College of Dentistry, 2011)
Aim of the Study: To compare the effects of stainless steel and nickel-titanium closed coil springs with the use of Roth bracket type and different arch wires on the amount of space closure during canine retraction in a Typodont simulation system. Material and Methods: Typodont system with Class II division 1 wax form and set of metal teeth, with Roth stainless steel brackets (0.022×0.030 inch) slot dimension. Eighty stainless steel readymade (Bonwill-Hawley arch form) arch wires divided in to two groups according to the size (0.019×0.025 inch and 0.020 inch), 40 for each size. Forty stainless steel and 40 nickel-titanium closed coil springs with force 200 gm. The distance between the distal wing of canine's bracket and the mesial end of second molar's tube was (31mm) which is the available space. Results: There was a significant difference in the rate of space closure between the two types of arch wires and between nickel titanium and stainless steel closing coil springs. Discussion: The rate of space closure significantly is greater with nickel-titanium closed coil spring. Nickel-titanium closed coil spring produce more sustained light continuous force. Conclusion: Nickel- titanium closed coil spring is an efficient material for canine retraction and space closure even with different wire sizes.